Discovery of a novel series of substituted quinolines acting as anticancer agents and selective EGFR blocker: Molecular docking study. (15th July 2021) - Kumar, C.B. Pradeep; Raghu, M.S.; Prathibha, B.S.; Prashanth, M.K.; Kanthimathi, G.; Kumar, K. Yogesh; Parashuram, L.; Alharthi, Fahad A.
Graphical abstract: Highlights: Novel quinolines were synthesized via direct amination approach using Ta2 O5 -functionalized-PPCA nanocatalyst. Cytotoxic activity was assessed against the panel of human cell lines. Compounds 5c and 5d showed good selectivity against EGFR-TK. The active compounds were subjected to molecular docking studies. Molecular docking and ADME predictions of active compounds shown as promising lead-like characters. Abstract: A Ta2 O5 -anchored-piperidine-4-carboxylic acid (PPCA) nanoparticle has been synthesized and characterized. It was then used as a highly effective nanocatalyst for the synthesis of quinolin-2(1H)-one derivatives through CO bond functionalization. The special advantage of this heterogeneous solid catalyst is the reusability of the catalyst for up to five cycles without any noticeable reduction in product yields. In comparison, healthy reaction profiles, wide substrate scope, excellent yields and easy workup conditions are the notable highlights of this approach. All the compounds were tested for their anticancer activity against MCF-7 (human breast), HepG2 (human liver), HCT116 (human colorectal), and PC-3 (human prostate) cancer cell lines with the MTT assay. All the compounds were shown to have moderate to good inhibitory effects on tested cancer cell lines. Besides, compounds 5b, 5c and 5d showed good selectivity against epidermal growth factor receptor-tyrosine kinase (EGFR-TK). Molecular docking results showed that active compounds showed a good affinity towards EGFR kinase (PDB ID: 6V6O) by forming two hydrogen bonds with Cys-797 and Tyr-801. All the compounds were screened for computational ADMET and Lipinski analysis.